2020
DOI: 10.1002/phar.2448
|View full text |Cite
|
Sign up to set email alerts
|

Using l‐Carnitine as a Pharmacologic Probe of the Interpatient and Metabolic Variability of Sepsis

Abstract: Objective The objective of this review is to discuss the therapeutic use and differential treatment response to Levo‐carnitine (l‐carnitine) treatment in septic shock, and to demonstrate common lessons learned that are important to the advancement of precision medicine approaches to sepsis. We propose that significant interpatient variability in the metabolic response to l‐carnitine and clinical outcomes can be used to elucidate the mechanistic underpinnings that contribute to sepsis heterogeneity. Methods A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…l -carnitine (lysine + methionine) is involved in beta-oxidation [ 29 ]. Its anti-inflammatory and antioxidant effects have already proven though its effects on septic patients are not conclusive [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…l -carnitine (lysine + methionine) is involved in beta-oxidation [ 29 ]. Its anti-inflammatory and antioxidant effects have already proven though its effects on septic patients are not conclusive [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The long-chain acylcarnitine C16:2(OH) was reduced in septic patients compared to SIRS [ 20 ], suggestive of reduced uptake of fatty acids into mitochondria as carnitines are involved in the transportation of long-chain fatty acids from cytoplasm [ 31 ]. In addition, studies focusing on adults and children also showed that patients with sepsis had increased levels of acetylcarnitine compared to SIRS [ 25 , 32 ] or healthy subjects [ 23 ], reflecting enhanced conversion of free carnitine and excess acetyl-CoA from metabolic stress into acetylcarnitine ( Figure 1 ) via carnitine acetyl-transferase [ 33 ]. Moreover, sugars including glucose, mannose and lactitol dehydrate were reduced in septic patients compared to SIRS [ 25 , 32 , 34 ] whilst sucrose was elevated [ 25 ].…”
Section: Metabolomics To Identify Diagnostically Useful Clinical Phen...mentioning
confidence: 99%
“…The study was powered to predict a posterior probability of the high dose (18 g) levocarnitine being superior to placebo, and only reached 0.78 rather than the 0.9 a priori benchmark. These results are confounded by the multitude of sepsis phenotypes, and variability in patient drug response to L-carnitine supplementation, several of the authors have suggested pharmacologic probes using L-carnitine to target subgroups of septic patients more likely to respond to therapy [ 144 ]. The variability of these data highlight the need for further research into pharmacogenomics and personalized medicine approaches to sepsis therapeutics.…”
Section: Lipid-based Therapiesmentioning
confidence: 99%